GÜNÜMÜZ KÜTÜPHANECİLİĞİNDE YENİ GELİŞMELER - Abdullah Demirtaş (Türk Kütüphaneciliği)
The ten basic points of view including new develepments in Library architerture, equipments and tools, computer techology, cultural and educational services of the libraries are abstracted from the literature and generalized to the observations. The article, develepments gradually are happening and/or may happen everwhere before the century is over.